Pharmacodynamics and Tolerance of Two Nadroparin Formulations (10,250 and 20,500 Anti Xa IU·ml-1) Delivered for 10 Days at Therapeutic Dose - Boneu, B.; Navarro, C.; Cambus, J. P.; Caplain, H.; d’Azemar, P.; Necciari, J.; Duret, J. P.; Gaud, C.; Sié, P. (Thrombosis and Haemostasis, 1998)
Venous thromboembolism may be efficiently treated by once-a-day (o.d.) administration of a high dose of low molecular weight heparin (LMWH) instead of administration of the same total dose in two injections a day (b.i. d.). To reduce the volume of the subcutaneous (s.c.) injection, a more concentrated form of the drug is advisable. This study was designed to compare the bioavailability of 2 formulations of nadroparin containing 10,250 and 20,500 anti-Xa IU·ml-1 respectively. This was an open, randomized, cross-over study where 12 healthy volunteers (age 18-35) were enrolled. They received either 90 anti-Xa IU·kg-1 b.i. d. of the 10,250 IU preparation (treatment A), or 180 anti-Xa IU·kg-1 o.d. of the 20,500 IU preparation (treatment B) for 10 days. On day 1, the subjects were sampled between 0 and 12 h (treatment A) or between 0 and 24 h (treatment B). On day 10, they were sampled between 0 and 12 h and between 12 and 24 h (treatment A) or between 0 and 24 h (treatment B). Anti-Xa and anti-IIa activities were determined by specific chromogenic assays. The main result of the study was that the bioavailability of the anti-Xa activity of the 2 nadroparin formulations was equivalent, as shown by the comparison of the AUC0-12 h plus AUC12-24 h (treatment A) and the AUC0-24 h (treatment B), calculated on day 10. This study also allowed a number of interesting observations to be made. 1) Between day 1 and day 10, there was an accumulation of the anti-Xa activity for treatment A but not for treatment B (accumulation factors: 1.6 and 1.1 respectively); 2) On day 10, the AUC0-12 h were slightly but significantly lower than the AUC12-24 h suggesting a circadian effect for anti-Xa and anti-IIa activities; 3) the clearance of the anti-Xa activity was comparable at the 2-dose regimens, while that of the anti-IIa activity was lower in treatment B than in treatment A, indicating a significant dose effect for the pharmacodynamics of the longer heparin chains; 4) On average, the clearance of the anti-IIa activity was twice as high as that of the anti-Xa activity; 5) For treatment B, significant APTT prolongations were noticed at Tmax (prolongation factor: 1.7 ± 0.25), in relation with the anti-IIa activity (0.3 ± 0.1 IU·ml–1).